Food addiction and associated factors in newly diagnosed patients with schizophrenia: a cross-sectional comparison with siblings and healthy controls - Feten Fekih-Romdhane; Youssef Boukadida; Abir Hakiri; Wided Homri; Majda Cheour; Souheil Hallit (Journal of Eating Disorders)
Abstract Background Despite the potential clinical and treatment relevance of food addiction (FA) among individuals with schizophrenia, the scientific literature on its characteristics and correlates within this population is sparse. Limited knowledge on FA in patients with schizophrenia may impede progress in developing effective treatments for pathological eating patterns and the common obesity and metabolic syndrome problems in this population. Considering these research gaps, the present study aimed to compare the nature and prevalence of FA symptoms among patients with first-episode schizophrenia, their siblings, and healthy controls. As a secondary objective, this study sought to examine the psychopathological correlates of FA in the patients’ group. Methods A cross-sectional study was conducted in Razi Hospital, Tunis, Tunisia, from January to June 2024. A total of 112 newly diagnosed, clinically stabilized patients with first-episode schizophrenia, 77 of their unaffected siblings and 78 healthy controls were included. FA was assessed using the modified version of the Yale Food Addiction Scale (mYFAS 2.0). The Metacognitions Questionnaire (MCQ-30) and the Emotion Regulation Questionnaire were administered to the patients’ group. Results Findings showed a higher prevalence of FA in the patient group (32.1%) compared to both siblings (13.0%) and controls (9.0%). Siblings had higher FA scores compared to controls (16.12 ± 4.95 versus 15.00 ± 6.09; p < 0.001). After Bonferroni correction for multiple testing, higher FA scores were significantly associated with less cognitive self-consciousness (Beta = − 0.54), older age (Beta = 0.45), and higher psychological distress (Beta = 0.63). Conclusion Our findings suggest that people with first-episode schizophrenia are likely to present with co-occurring FA, and experience associated distress. Findings also provide initial support for a possible connection between dysfunctional metacognitive beliefs and FA in patients with schizophrenia, suggesting that cognitive self-consciousness may be a fundamental cognitive process in FA in this population. This may lend some theoretical and clinical implications for alleviating FA symptoms in schizophrenia.